Prognostication of Half-Life Clearance of Plasma EBV DNA in Previously Untreated Non-metastatic Nasopharyngeal Carcinoma Treated With Radical Intensity-Modulated Radiation Therapy - Sik-Kwan Chan; Sum-Yin Chan; Horace Cheuk-Wai Choi; Chi-Chung Tong; Ka-On Lam; Ka-On Lam; Dora Lai-Wan Kwong; Dora Lai-Wan Kwong; Varut Vardhanabhuti; To-Wai Leung; To-Wai Leung; Mai-Yee Luk; et al. (Frontiers in Oncology, 2020)
Introduction: The prognostic role of plasma Epstein–Barr virus (EBV) DNA clearance when intensity-modulated radiotherapy (IMRT) and the 8th edition of American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) TNM Staging Classification are fully implemented remains undeciphered. We investigated if its half-life clearance during radical treatment for non-metastatic nasopharyngeal carcinoma (NPC) was an early prognosticator.Patients and methods: Patients with previously untreated non-metastatic NPC were prospectively treated with radical IMRT and concurrent chemotherapy +/– induction/adjuvant chemotherapy from 2014 to 2018. Their plasma EBV DNA was measured immediately before treatment followed by weekly schedules until 0 copy/ml in two consecutive measurements. Cox regression models were employed to identify prognostic factors.Results: Forty-five patients were prospectively recruited and analyzed. After a median follow-up of 30.3 months, 2 (4.5%), 1 (2.3%), and 6 (13.6%) patients experienced local, regional, and distant relapses, respectively. The median half-life clearance of plasma EBV DNA was 7.92 days. Those with half-life clearance of >15 days had a worse 3-years progression-free survival (PFS) (79.5 vs. 25.0%, p = 0.005), distant metastasis-free survival (DMFS) (85.0 vs. 31.3%, p = 0.009), and overall survival (OS) (91.3 vs. 75.0%, p = 0.024) when compared to those with a shorter half-life. Multivariable analyses demonstrated that only half-life (>15 days) was prognostic of DMFS [HR (95% CI): 4.91 (1.31; 18.39), p = 0.01] and OS [HR (95% CI): 5.24 (1.06; 26.05)] while half-life (>15 days) [HR (95% CI): 5.14 (1.28; 22.73), p = 0.02] and sum of pretreatment gross tumor volumes of the primary nasopharyngeal tumor and the radiologically positive neck nodes (GTV_P+N) [HR (95% CI): 1.01 (1.00; 1.03), p = 0.02] were prognostic of PFS.Conclusion: The half-life clearance of plasma EBV DNA was prognostic in non-metastatic NPC staged and treated in the contemporary era. Earlier biomarker surveillance during treatment should be considered.Clinical Trial Registration: This study has been registered with ClinicalTrials.gov (Identifier: NCT03830996).